ADVERSITY, MENTAL HEALTH, AND SUBSTANCE USE DISORDERS AS PREDICTORS AND MEDIATORS OF RULE VIOLATIONS IN U.S. PRISONS - HENRY, BRANDY F. (Crim Justice Behav, 2019)
This study explores how typologies of adversity and mental health/substance use disorders impact rule violations during incarceration. Data come from the 2004 cross-sectional Survey of Inmates in State and Federal Correctional Facilities (SI-SFCF). Logistic regression and structural equation modeling were used for analysis. Results link history of adverse experiences to rule violations during incarceration and demonstrate how mental health and substance use disorders mediate this relationship. Incarcerated people with severe histories of adverse experiences had the highest odds of rule violations, relative to people with low adversity, for all typologies. More severe adversity typologies predicted mental health and substance use disorders. Alcohol and substance use disorders predicted drug violations, whereas substance use and mental health disorders predicted major violations. Serious mental illness did not predict rule violations when accounting for adversity. Findings suggest that addressing adverse experiences, mental health, and substance use disorders may prevent rule violations.